Evaluation of Three Different Forward Primers by Terminal Restriction Fragment Length Polymorphism Analysis for Determination of Fecal Bifidobacterium Spp. in Healthy Subjects - Hayashi, Hidenori; Sakamoto, Mitsuo; Benno, Yoshimi (Microbiology and immunology, 2004)
The 27F forward primer is frequently used in 16S rRNA gene libraries and T‐RFLP analysis. However, Bifidobacterium spp. were barely detected with this primer in human fecal samples. In this study, fecal microbiota were analyzed using the T‐RFLP method with three different forward primers (27F, 35F, and 529F) in conjunction with one reverse primer (1492R). T‐RFLP analysis of fecal microbiota using 35F and 529F detected higher proportions of the terminal restriction fragment (T‐RF) corresponding to Bifidobacterium spp. than that using 27F. 27F is in imperfect agreement while 35F and 529F are in good concordance with the 16S rRNA gene sequences of Bifidobacterium spp., and the latter primers allowed for the detection of T‐RFs of Bifidobacterium spp. in fecal samples from five healthy subjects. The T‐RFs presumed to be Bifidobacterium spp. were cloned and sequenced, and found to match the 16S rRNA gene sequences of Bifidobacterium spp. Among the five fecal samples, two samples with low frequencies of T‐RFs of Bifidobacterium spp. were detected using these forward primers. This probably reflects a low prevalence of Bifidobacterium spp. in these two samples. Our study emphasizes the importance of selecting a suitable forward primer for detection of Bifidobacterium spp.